PERTANGGUNGJAWABAN PELAKU TINDAK PIDANA MENYERANG KEHORMATAN SUSILA: Studi Putusan Nomor 641/Pid.B/2021/PN.Tjk - Valen Nababan; Baharudin Baharudin; Anggalana Anggalana (LPPM Universitas Bina Bangsa, 2022)
The crime of decency is similar to the criminal act of attacking the honor of immorality that occurs in the tanjungkarang district court rules area, is the impact of children's freedom in association or even mistakes in associating in the community. The problem in this writing is how the accountability of criminals attacks the honor of immorality based on Verdict number 641 / Pid.B / 2021 / PN.Tjk and what are the basis of the judge's consideration in handing down the verdict against the perpetrator of the criminal act of attacking immoral honor in accordance with the figure of Verdict 641 / Pid.B / 2021 / PN.Tjk. The approach method used in this study is a normative juridical approach and a reality approach. Data collection according to literature studies and field studies, while data processing is done using methods of editing, classification and systematization of data, then analyzed using qualitative descriptive analysis. In accordance with what will happen, it will be seen that the accountability of criminals to attack moral honor in accordance with Verdict number 641 / Pid.B / 2021 / PN.Tjk which is declared valid and convincingly proven as guilty in the single indictment in Article 286 with imprisonment for 4 (four) years. Furthermore, the basis of the judge's consideration on handing down the verdict against the perpetrators of criminal acts attacks the honor of immorality based on Verdict number 641 / Pid.B / 2021 / PN.Tjk consists of several juridical and non juridical aspects. The juridical aspects are the prosecution's demands and indictments, the sense of evidence, and the information of the rules revealed during the trial examination process. The advice in this study is that parents should be supervised on the behavior of their children, especially from the adverse consequences of association in the environment of their home area, so as to minimize the occurrence of criminal acts committed by the child